Esrαexon polymorphism coupled with proteinModelling in relation to reproductiveTraits in murrah buffaloes - SARLA RANI; MAHESH KUMAR; PRADEEP KUMAR NAIK; S K PHULIA; VINOD CHHOKAR (International Journal of Pharma and Bio Sciences, 2016)
Buffalo plays a pivotal role in livestock and agriculture economy of many countries across the world. Estrogen receptor (ESR) has been known to play crucial role in the development of feminine secondary sexual characteristics as well as in the female reproductive cycle, infertility, and maintenance of pregnancy. The present study was aimed to test the hypothesis that polymorphism at ESR loci has some association with reproductive traits of buffaloes that can be used as a marker for reproductive efficiency in marker assisted selection. Sixty five Murrah buffaloes were selected and divided in to six groups on the basis of their physiological data. We found high genetic variation ranges from 0% to 5.2% in the nucleotide sequence of ESR gene among different groups of buffalos. In contrast 0% to 16.24% variation was found in the translated protein sequence of ESR gene from different groups of buffalos. Only two SNPs were observed at 64 (T→G) and at 68 (T→G) in field abnormal group animals. Entropy plots also confirmed the genetic variation via peaks and the area covered by those peaks. Homology model of protein from different groups of buffaloes were constructed and compared to find out the impact of SNPs in the overall structure of translated protein of ESR. The pair wise comparison of protein structure varies from 0.642 to 1.818 (expressed as root square mean deviation, RSMD). PCR-RFLP coupled with protein modelling showed variation at amino acid level and very little variation was also observed in 3-D protein structures.